Clinical features of endophthalmitis clusters after cataract surgery and practical recommendations to mitigate risk: systematic review. Issue 1 (January 2022) - Park, Jeff; Popovic, Marko M.; Balas, Michael; El-Defrawy, Sherif R.; Alaei, Ravin; Kertes, Peter J.
Abstract : This review examines the clinical features of endophthalmitis clusters and characteristics of pathogen transmission after cataract surgery. Recommendations for detection, prevention, and management of endophthalmitis clusters are highlighted. Abstract : Intraocular transmission of exogenous pathogens in cataract surgery can lead to endophthalmitis. This review evaluates the features of endophthalmitis clusters secondary to pathogen transmission in cataract surgery. Articles reporting on pathogen transmission in cataract surgery were identified via searches of Ovid MEDLINE, EMBASE, and Cochrane CENTRAL, and a total of 268 eyes from 24 studies were included. The most common source of infectious transmission was attributed to a contaminated intraocular solution (ie, irrigation solution, viscoelastic, or diluted antibiotic; n = 10). Visual acuity at presentation with infectious features was 1.89 logMAR (range: 1.35 to 2.58; ∼counting fingers) and 1.33 logMAR (range: 0.04 to 3.00; Snellen: ∼20/430) at last follow-up. Patients with diabetes had worse outcomes compared with patients without diabetes. The most frequently isolated pathogen from the infectious sources was Pseudomonas sp. (50.0%). This review highlights the various routes of pathogen transmission during cataract surgery and summarizes recommendations for the detection, prevention, and management of endophthalmitis clusters.